Climate change‐induced vegetation shifts lead to more ecological droughts despite projected rainfall increases in many global temperate drylands. (6th March 2017) - Tietjen, Britta; Schlaepfer, Daniel R.; Bradford, John B.; Lauenroth, William K.; Hall, Sonia A.; Duniway, Michael C.; Hochstrasser, Tamara; Jia, Gensuo; Munson, Seth M.; Pyke, David A.; Wilson, Scott D.
Abstract: Drylands occur worldwide and are particularly vulnerable to climate change because dryland ecosystems depend directly on soil water availability that may become increasingly limited as temperatures rise. Climate change will both directly impact soil water availability and change plant biomass, with resulting indirect feedbacks on soil moisture. Thus, the net impact of direct and indirect climate change effects on soil moisture requires better understanding. We used the ecohydrological simulation model SOILWAT at sites from temperate dryland ecosystems around the globe to disentangle the contributions of direct climate change effects and of additional indirect, climate change‐induced changes in vegetation on soil water availability. We simulated current and future climate conditions projected by 16 GCMs under RCP 4.5 and RCP 8.5 for the end of the century. We determined shifts in water availability due to climate change alone and due to combined changes of climate and the growth form and biomass of vegetation. Vegetation change will mostly exacerbate low soil water availability in regions already expected to suffer from negative direct impacts of climate change (with the two RCP scenarios giving us qualitatively similar effects). By contrast, in regions that will likely experience increased water availability due to climate change alone, vegetation changes will counteract these increases due to increased water losses by interception. In only a small minority of locations, climate change‐induced vegetation changes may lead to a net increase in water availability. These results suggest that changes in vegetation in response to climate change may exacerbate drought conditions and may dampen the effects of increased precipitation, that is, leading to more ecological droughts despite higher precipitation in some regions. Our results underscore the value of considering indirect effects of climate change on vegetation when assessing future soil moisture conditions in water‐limited ecosystems. Abstract : We used the ecohydrological model SOILWAT to explore the impact of climate change‐induced changes in vegetation cover and composition on soil water availability. We found that for many sites, vegetation changes are likely to lead to a decrease in soil water availability. This can lead to more ecological droughts despite higher rainfall. The negative impact of vegetation on soil water availability increases with a higher change in vegetation biomass.